How do we increase the share of aid to agriculture in Africa? - Peter Quartey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Agriculture plays an important role in terms of employment and its contribution to gross domestic product in many African countries. Thus, any policy initiative targeted towards poverty reduction in Africa should consider the agricultural sector as the major priority area. Unfortunately, the sector faces a myriad of challenges and prominent among them is the issue of finance. Although some significant amounts of agricultural finance has come from official development assistance (ODA), private capital flows, and private philanthropy, it has been argued that the scale has not been adequate to transform the sector into a modern and highly productive sector. For instance, data from Organization for Economic Co-operation and Development show that in 2009, of the total ODA from the Development Assistance Committee countries, only six per cent went into agriculture, forestry, and fishing, while education received 10.3 per cent, population and reproductive health 11.5 per cent, and humanitarian 11.9 per cent. Using secondary data and country-case studies from Africa, the study investigates why aid to agriculture has been low, and how the share of ODA to agriculture can be improved.
Keywords: E22; F34; F35; Q1; 330; aid; agriculture; Africa; poverty